Монети Цареборисівської фортеці - Голубєва, І.В. (My University, 2005)
I. Golubeva. The Coins of Czareborysivska Fortress The article contains an ascription of numismatics material obtained in the course of 2004 explorations on the territory of Czareborysivska hillford. The table and drawings display systematized coins of Moscow state (Ivan the Terrible, Phedor Ivanovich, Boris Godunov, Mikhail Phedorovich and Alexei Mikhailovich), coins from the Baltic territories of Sweden (Gustav Adolph, Christina Augusta, Karl X Gustav and Karl XI), coins of Rich Pospolita (Sigizmund III Vaza and Jan Kasimir) and coins of the Crimean khanate (Muhammad Girei IV). The analysis of the represented coins confirms ethnic affiliation of the fortress’s population, which is stated in archive sources, as well as enables making amendments to the existing chronology of fortress’s functions.